A finite element analysis on mechanical behavior of Al/Al-Mg composites for the design of tank cars under actual measuring loads. (September 2019) - Yang, G.X.; Fu, D.L.; Li, Q.; Liu, Z.M.
Abstract: The transportation safety of tank cars carrying concentrated nitric acids under conditions of heavy loads has attracted the increasing attention. The use of Aluminum/Aluminum-Magnesium(Al/Al-Mg) alloys to form laminated composites can solve the problems associated with the low corrosion resistance and strength of tank car bodies. In this work, a finite element analysis was used to simulate the tensile tests of the Al/Al-Mg laminated composites. In particular, the stress and strain behavior of the composites under tensile loads was investigated, and the corresponding mechanical properties of the composites were determined, which was verified by the tension test results. Furthermore, the effective load time history was obtained by processing the measuring data of C70E type gondola car body on three typical general railway line. Load spectra of car body were compiled using the rain-flow count method, which was applied to do the fatigue design for 70 t Al/Al-Mg tank body. Most importantly, in conjunction with the SN curve of the base materials and the lap-welded joint, based on the tank car finite element analysis results under various load cases, the fatigue life of the 70 t Al/Al-Mg tank body was calculated based on Miner's linear accumulative damage theory. The results showed a very promising application of such composite materials to meet the safety requirements. Highlights: The stress-cycle curve with a survival rate of 97.7% was obtained; The fatigue failure of the laminated plate was determined. The fatigue life of the tank body was calculated based on Miner's linear cumulative damage theory.